Estrategias de aprendizaje y pensamiento histrico en los estudiantes del primer ao de secundaria de la Institucin Educativa "1255" 2020 - Cruz Rojas, John Edvin (2022)
The present investigation had as general objective to determine the relationship that exists between learning strategies and historical thinking in the students of the first year of secondary school of the Educational Institution "1255" in Huaycn - Lima, during the year 2020. The investigation carried out was non-experimental quantitative type with a correlational design. The population was made up of 129 students in the first year of high school, while the sample selected for this research was 62 students belonging to three sections of said educational institution: "A", "Extended 1" and "Extended 2". The technique used was the survey and the instrument were a questionnaire, which was validated by expert judgment and with a reliability of Cronbach's Alpha of 0.790. The questionnaire consisted of 22 items and was used to measure the relationship between the variables learning strategies and historical thinking, as well as between their respective dimensions. In this way, the results obtained were subjected to the processing and interpretation of data through the statistical package SPSS version 25. Through this research it was concluded that there is a moderate positive relationship between learning strategies and historical thinking in students of the first year of high school of the Educational Institution "1255" in the year 2020, because a Pearson Correlation of 0.671 was obtained.